E-083 Intraarterial and intravenous abciximab for management of acute in-situ thrombosis during pipeline flow diversion of intracranial aneurysms. (23rd July 2017) - Jiang, B; Campos, J; Beaty, N; Westbroek, E; Bender, M; Tamargo, R; Huang, J; Colby, G; Coon, A; Lin, L
Abstract : Background: Flow diversion is an effective and increasingly accepted method for endovascular treatment of cerebral aneurysms. Acute in-situ thrombosis during Pipeline embolization device (PED) deployment has potential for devastating morbidity. There is limited experience in the flow diversion literature on the usage of Abciximab (ReoPro) to address this issue. Methods: Data were collected retrospectively on patients who encountered in-situ thrombosis during Pipeline flow diversion of anterior and/or posterior circulation intracranial aneurysms. Data collected include aneurysms characteristics, Abciximab dosing and administration regimen, post-procedural antiplatelet therapy, and clinical/radiographical follow up. Results: Twenty-five patients (mean age 56 years; range 36–75 years) with 26 unruptured aneurysms (mean size 8.7 mm; range 2-25 mm) were identified to have in-situ thrombosis during PED deployment. Intraarterial (IA) ReoPro was administered in all cases, with 15 patients receiving increments of 5mg boluses and 10 patients receiving 0.125mg/kg bolus. Immediate or partial resolution of in-situ thrombosis was observed in 100% of the patients. Intravenous (IV) ReoPro infusion was administered post-procedurally in 18 patients. 19 patients were transitioned to Prasugrel (Effient) from Clopidogrel (Plavix) post procedurally. Average length of stay was 4.5 days (range 1-30 days), with 21/26 (81%) patients discharged to home. Intracranial hemorrhage was noted in 2 patients (8%). At six-months clinical follow up, 20/25 (80%) patients had mRS of 0. Angiographic follow up was available for 18 patients at a mean duration of 9.6 months, at which time aneurysm occlusion rate was 94% (16/17 patients). Conclusions: IA and IV ReoPro administration is a effective and safe strategy for the management of acute in-situ thrombosis during PED, with high rates of immediate thrombosis resolution and relatively low rates of hemorrhagic complications and long term morbidity. Disclosures: B. Jiang: None. J. Campos: None. N. Beaty: None. E. Westbroek: None. M. Bender: None. R. Tamargo: None. J. Huang: 2; C; Longeviti. G. Colby: 1; C; Stryker. 2; C; Microvention, Medtronic. A. Coon: 2; C; Medtronic, Microvention, Sequent, Stryker. L. Lin: None.